2006
DOI: 10.1111/j.1440-1746.2006.04375.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rifabutin‐based triple therapy in Helicobacter pylori infected patients after two standard treatments

Abstract: The eradication rate is acceptable as a third-line therapy, particularly in centers with high cure rate for first line therapy. Another important value of this study is the good tolerance for the treatment observed in our patients. It is possible that rifabutin-based triple therapy may be of use in hospital centers that do not have disposable culture and susceptibility methods against H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…Little has been reported on rifabutin resistance in clinical practice. Eradication rates with a rifabutin-based regimen (rifabutin + amoxicillin + PPI) have been reported in the range of 62 -86% when used as salvage therapy after one or more previous eradication attempts [71][72][73] . A recent study using rifabutin triple therapy (rifabutin 150 mg b.i.d.…”
Section: Rifabutinmentioning
confidence: 99%
“…Little has been reported on rifabutin resistance in clinical practice. Eradication rates with a rifabutin-based regimen (rifabutin + amoxicillin + PPI) have been reported in the range of 62 -86% when used as salvage therapy after one or more previous eradication attempts [71][72][73] . A recent study using rifabutin triple therapy (rifabutin 150 mg b.i.d.…”
Section: Rifabutinmentioning
confidence: 99%
“…Thus, until now, no rifabutin resistant strain has been isolated from patients who were either treated or untreated for H pylori infection [166] . As summarized Table 2, rifabutin-based rescue therapy constitutes an encouraging strategy after multiple previous eradication failures [63,72,130,149,[151][152][153]155,[169][170][171][172] . As an example, Perri et al [151,173] used a 1-wk regimen of PPI, amoxicillin and rifabutin in patients who were still H pylori infected after two or more courses of PPI-based triple therapies, and achieved an eradication rate of 71% by intention-to-treat analysis.…”
Section: Rifabutin-based Rescue Regimensmentioning
confidence: 99%
“…However, these encouraging results were not confirmed in a more recent study by these same authors [155] . In the largest study on rifabutin [170] , 92 consecutive patients diagnosed with H pylori infection resistant to two previous treatment regimens were treated with a PPI, rifabutin and amoxicillin for 10 d and the intention-to-treat eradication rate was 61%. In summary, the weighted mean eradication rate with rifabutin-based rescue therapy, calculated from the studies included in the Table 2, is 69%.…”
Section: Gisbert Jp Rescue Regimens For H Pylori 5393mentioning
confidence: 99%
“…Another candidate for a third-line regimen is rifabutin (RFB). It is reported that RFB-based triple therapy is effective for H. pylori eradication in Spain [8]. RFB is an anti-tuberculosis agent derived from rifamycin-S and structurally similar to rifampicin (RFP), which is also a rifamycin-S derivative.…”
Section: Introductionmentioning
confidence: 99%